Analisis Manajemen Strategi Pada UMKM Eka Jaya Mandiri Dalam Menghadapi Persaingan Bisnis - Saragih Sidauruk, Jhon Erikson; Astuti, Dwi (CV. ITTC INDONESIA, 2025)
This qualitative research aims to analyze the strategic management practices of UMKM Eka Jaya Mandiri, a wood furniture micro-enterprise, in facing business competition. The study was motivated by the increasing hype in the wood furniture industry and the strategic challenges frequently faced by small enterprises, such as inconsistent sales performance and limited marketing capabilities. Data were collected through in-depth interviews, observation, and documentation. The sales trend throughout 2024 showed fluctuating performance, ranging from IDR 28 million to IDR 50 million per month, indicating the absence of a consistent and adaptive strategy. The findings reveal that the business relies heavily on intuition and lacks structured planning, digital marketing efforts, and formal organizational systems. These weaknesses limit the enterprise’s ability to respond to market dynamics and competition effectively. This research suggests the need for capacity building in strategic planning, digital transformation, and organizational development to ensure sustainable competitiveness. The results are in line with relevant strategic management literature that emphasizes the importance of environmental analysis, strategic implementation, and continuous evaluation for small business success.